2015
DOI: 10.1016/j.apradiso.2014.12.029
|View full text |Cite
|
Sign up to set email alerts
|

New activation cross section data on longer lived radio-nuclei produced in proton induced nuclear reaction on zirconium

Abstract: In the frame of a systematic study of charged particle production routes of medically relevant radionuclei, the excitation function for indirect production of 178m Ta through nat Hf(α,xn) 178−178m Ta nuclear reaction was measured for the first time up to 40 MeV. In parallel, the side reactions nat Hf(α,x) 179,177,176,175 W, 183,182,178g,177,176,175 Ta, 179m,177m,175 Hf were also assessed. Stacked foil irradiation technique and γ-ray spectrometry were used. New experimental cross section data for the nat Ta(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Since then, many groups have repeatedly investigated this reaction for production, but no new cross-section measurement has been done. For the nat Rb( 3 He,xn) 86 Y reaction, also cross-sections were measured only once [15], but for the nat Zr(p,x) 86 Y reaction, a few new measurements have been reported over the last few years [17,18,19,20]. Very recently, cross-section data for a few reactions have been evaluated using rigorous nuclear model calculations, and recommended data have been presented [21].…”
Section: Nuclear Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, many groups have repeatedly investigated this reaction for production, but no new cross-section measurement has been done. For the nat Rb( 3 He,xn) 86 Y reaction, also cross-sections were measured only once [15], but for the nat Zr(p,x) 86 Y reaction, a few new measurements have been reported over the last few years [17,18,19,20]. Very recently, cross-section data for a few reactions have been evaluated using rigorous nuclear model calculations, and recommended data have been presented [21].…”
Section: Nuclear Datamentioning
confidence: 99%
“…Similarly, in the nat Zr(p,x) 86 Y process, the level of the 87 Y impurity formed via the 90 Zr(p,α) 87 Y reaction could be minimized if the incident protons have energies >25 MeV where the 90 Zr(p,αn) 86 Y reaction is favored. We therefore show the integral yields of 86 Y in Figure 2 also from those reactions, taking the data for the nat Rb( 3 He,xn) 86 Y process from [15] and those for the nat Zr(p,x) 86 Y process from [17,18,19,20,21]. It should be mentioned that in the case of the latter two reactions, the use of highly enriched 85 Rb and 9 0 Zr as targets would increase the 86 Y yield by about 25 and 100%, respectively, but it would not alter the radioactive impurity level to any significant extent, provided the energy ranges used in the targets are the same as given in Table 2 (see below).…”
Section: Nuclear Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we report the excitation function for the production of 96 Nb on natural zirconium targets bombarded by a proton beam with energies in the range from 10.58 to 43.61 MeV. In the literature, we have found some publications on the excitation function of the nat Zr(p,x) 96 Nb reaction [6][7][8][9][10][11]. It has been shown that the consistency between the reported data is good at proton energies below about 10 MeV, but poor at higher energies.…”
Section: Introductionmentioning
confidence: 99%